Characterization of cocoa (theobroma cacao l.) farming systems in the norte de santander department and assessment their sustainability / caracterización de los sistemas de producción de cacao (theobroma cacao l.) en el departamento de norte de santander (2014)
The cocoa (Theobroma cacao L.) based economyhas been considered a valid alternative to support sustainable development in northeastern Colombia. However, there is a lack of information about the cocoa production systems in the region which is needed for the implementation of effective plans to improve their performance and sustainability. Four of the main cocoa producing municipalities in the Norte de Santanderdepartment were considered for this study: Teorama, Bucarasica, Cúcuta and San Calixto. These entities were selected due to their adequate security conditions, availability of field assistants and departmental representativeness in cocoa production. The objective was to obtain basic information for local, specific and participatory actions for the sustainability of the cocoa production systems and to improve the living conditions of farmers. The methodology used was based on the farming system approach, considering the socioeconomic, technological and agro-ecologicalcomponents, and their relationships, and evaluating themaccording to the principles of sustainable agriculture. The phases covered were: (1) analysis of secondary data, (2) formulation and evaluation of sustainability indicators, (3) design, implementation and analysis of survey data and (4) validation by the farmers of the obtained information and the prioritization of problems. The results indicate that there is only one cocoa production system of a family-mercantile type, with low technology. Most farmers havelow incomes and basic needs such as health, education and public services are not met. They do not employ the agronomic and postharvest practices recommended by specialists. The water and soil resources are being degraded. In general, the farming system leans towards unsustainability and it is vital that integrative actions be taken to change this situation. / Se considera que el desarrollo de una economía basada en el cacao (Theobroma cacao L.) constituye una alternativa válida para impulsar el desarrollo sostenible en el noreste colombiano. Sin embargo, se carece de la información básica necesaria sobre los sistemas de producción de cacao para la instrumentación de planes que permitan mejorar su desempeño y sostenibilidad. Para este estudio, se consideraron cuatro municipios del departamento de Norte de Santander: Teorama, Bucarasica, Cúcuta y San Calixto, los cuales fueron seleccionados debido a que poseen condiciones adecuadas de seguridad, asistentes de campo y son representativos del departamento en cuanto a  roducción de cacao. El objetivo fue obtener información básica para la toma de acciones locales, específicas y participativas hacia la sostenibilidad de los sistemas de producción de cacao, considerando los componentes socio-económicos, tecnológicos y agroecológicos, y sus relaciones, evaluándolos de acuerdo a los principios de la agricultura sostenible. Se realizaron cuatro etapas: (1) análisis de datos secundarios, (2) formulación y evaluación de indicadores de sostenibilidad, (3) diseño, instrumentación y análisis de los datos de la encuesta y (4) validación por los agricultores de la información obtenida y priorización de problemas. Los resultados indican que hay un solo sistema de producción de cacao del tipo familiar-mercantil de baja tecnología. La mayor parte de los productores reciben bajos ingresos y las necesidades básicas de salud, educación y servicios públicos no están satisfechas. Los recursos de suelo y agua se están degradando. En general, el sistema de producción tiende a la insostenibilidad y se requieren acciones integrales para cambiar esta situación.